Tren dan Tantangan Adopsi Teknologi Informasi di Industri Manufaktur Tekstil dan Garmen (Systematic Literature Review) - Imran, Nungky Amalia (Akademi Komunitas Industri Tekstil Dan Produk Tekstil Surakarta, 2025)
The impact of information technology developments has influenced various business processes in many fields, including the textile and garment manufacturing industry. The application of technologies such as Enterprise Resource Planning (ERP), Internet of Things (IoT), Artificial Intelligence (AI), Big Data Analytics, and automation systems has increased production efficiency, optimized supply chains, and enabled data-based decision-making. This research aims to analyze various trends, opportunities, and challenges in the application and use of information technology in textile and garment manufacturing companies to provide a comprehensive overview of this industry. A systematic literature review was conducted by analyzing articles related to the research topic. The final results of the study indicate that digitalization is the most widely adopted technology in the textile and garment sector. Several other technological innovations have not been widely adopted, indicating that there are still opportunities that can be developed so that the use of information technology in the industry can be maximized.